Membrane technologyfor the treatment of fish industry effluent - Ponsano, Elisa Helena Giglio [UNESP]; Pires, Helenice Aparecida [UNESP]; Oliveira, Dayse Lícia [UNESP]; Garcia, Andréa Fontes (My University, 2018)
Membrane filtration emerges as an alternative for the treatment of fish processing effluent. The aim of this work was to verify the ability of membrane filtration on reducing the pollutant load of tilapia processing effluent. The filtrations were performed with 150, 30 and 10 kDa membranes. The physicochemical parameters of the effluent in natura and the permeates were compared among themselves and with the standards for launching foreseen in the Brazilian legislation to evaluate the possibility of direct disposal in water bodies. The three membranes had the same potential to remove total solids, nitrogen and nitrite from the effluent. Membranes 30 and 10 kDa caused similar effects on the removal of Chemical Oxygen Demand and proteins. Oils and greases, pH and fixed solids did not change with the filtrations. All the membranes were effective in reducing the color of the effluent. The effluent in natura was already in agreement with the standards for discharge regarding to temperature, pH, total nitrogen and nitrite, and the use of the membranes allowed it to meet the standards for floating materials. The color and the content of oils and grease in permeates were above the levels allowed for the discharge in freshwater, so suggesting the use of an additional operation to comply with the legislation.
Tecnologia de membranas no tratamento de efluente de indústria de pescado
Keywords: Chemical oxygen demand; Proteins; Total solids; Ultrafiltration